Amperometric detection of sulfide at a boron doped diamond electrode: The electrocatalytic reaction of sulfide with ferricyanide in aqueous solution. - Lawrence, N; Thompson, M; Prado, C; Jiang, L; Jones, T; Compton, R (2002)
The oxidation of sulfide at a boron doped diamond (BDD) electrode has been examined and its analytical utility appraised and compared with other common electrode substrates (Pt, Au, glassy carbon). The suitability of using BDD as a sulfide sensing substrate has been assessed through examining the electrocatalytic oxidation of ferrocyanide to ferricyanide in the presence of sulfide using both cyclic voltammetry and chronoamperometry. The high oxidation potential for the direct oxidation of sulfide at a BDD electrode allows clear resolution of both the ferrocyanide wave and sulfide oxidation wave producing a distinct analytical signal at the oxidation peak potential of ferrocyanide. The procedure was applied to the recovery of a sulfide spike in sewage effluents with a recovery of 102 ± 4.5%.